Research Brief One-Sheet No.1: Late-Stage Police Crime: Is it an Exit Strategy? - Freiburger, Tina L (2012)
The study focuses on crimes committed by experienced police officers who are approaching retirement. Police scholars have traditionally been interested in the formative experiences that occur near the beginning of an officer's career, wherein the expectations of rookie cops clash with on-the-job realities to promote cynicism, personal anomia, and potential attachment to delinquent police subcultures. The literature suggests that officers will tend to get into trouble earlier in their career rather than later; but, the occurrence of late-stage misconduct committed by experienced police officers presents a challenge to existing assumptions regarding the relationship between experience and various forms of police misconduct and also provides an opportunity to examine a stage of the police career that has not been the subject of much research